(untitled) (Journal of the College of Basic Education, 2023)
The importance of the creative writing skill appears in the impact it achieves in building the student’s personality, as it contributes to his evaluation socially, intellectually, and psychologically, and therefore this study sought to search for how to develop it, and the researcher used lateral thinking strategies, which he assumed that it has an effective role in developing the skill of creative writing among fifth grade literary students, and the procedures of the semi-experimental approach were followed, as the researcher adopted an experimental design with partial control, and he randomly chose Al-Karama Preparatory School for Boys to be The research sample, in the same way, chose Division (A) to represent the experimental group by (31) students, and Division (B) to represent the control group by (32) students, then the researcher rewarded between the students of the two research groups a statistical equivalence in: (chronological age, academic achievement of parents, language ability test, and creative writing test), and as for the research tool, the researcher built his test in creative writing skills on the type of essays, and he verified the sincerity and stability of the test after presenting it to a group of arbitrators, and after conducting the experiment, the test was applied to Students of the research sample, after processing the data statistically .